Glassy-state high-purity quartz sand and preparation method thereof
By preparing the method of high -pure quartz sand in the glass state, the nano -grade unsecured silicon oxide is used for slurry, spray drying, mechanical static pressure, mechanical crushing and burning, which solves the complex, time -consuming and long -term purity of high -pure quartz sand purification technology The introduction of impurities has achieved high purity and efficient quartz sand preparation.
Patent Information
- Application Number
- CN202411265000.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2025-01-24
AI Technical Summary
The existing high-purity quartz sand purification process is complex, time-consuming, easy to introduce exogenous impurities, and a large amount of harmful wastewater is generated during the pickling process, increasing the treatment cost.
Using nanoscale amorphous silica as raw material, glassy high-purity quartz sand is prepared through steps such as pulping, spray drying, mechanical static pressing, mechanical crushing and calcination.
The operation was simple and easy to control. The SIO2 content reached more than 99.998 %, and the indicator of the existing natural high pure quartz sand than the surface area and density reached the existing natural high pure quartz sand, which avoided the introduction of exogenous impurities and the production of harmful wastewater.
Smart Images

Figure CN119349589A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of quartz sand processing, and in particular to glassy high-purity quartz sand and a preparation method thereof. Background Art
[0002] High-purity quartz sand usually refers to quartz with a silicon dioxide content greater than 99.9%. According to the SiO2 purity, high-purity quartz products can be divided into four grades, namely high-end ω (SiO2) ≥ 99.998% (4N8), mid-to-high-end ω (SiO2) ≥ 99.995% (4N5), mid-end ω (SiO2) ≥ 99.99% (4N), and low-end ω (SiO2) ≥ 99.9% (3N). However, it is difficult for unprocessed natural quartz to meet the quality requirements of high-purity quartz. In other words, high-purity quartz sand is a quartz sand product with extremely high SiO2 purity obtained by using natural quartz ore as raw material and undergoing a relatively complex purification process.
[0003] The impurity elements in natural quartz sand mainly include Al, K, Na, Li, Ca, Cu, B, Fe, Mn, Co, Ti, P, etc. Among these impurity elements, monovalent and divalent ions exist in the form of interstitial atoms at the charge imbalance defects in the quartz lattice. As compensation charges, trivalent, tetravalent, and pentavalent ions (isomorphic impurities) mainly exist in the lattice. In order to remove impurities in quartz sand, technicians have proposed a variety of processes. Zhang Haiqi et al. recorded the existing quartz sand purification technology in the article "Research Progress on Impurity Characteristics and Deep Chemical Purification Technology in High-Purity Quartz" (Mineral Protection and Utilization, August 2022, Issue 4). At present, the main methods for purifying natural quartz sand mainly include physical and chemical methods. Physical purification mainly includes color sorting, scrubbing, gravity separation, magnetic separation and flotation processes, but gas-liquid inclusions and isomorphic impurities inside the lattice are the main sources of impurities, and these impurities are the key factors restricting the preparation of high-purity quartz products. Physical purification cannot remove these impurities, so chemical deep purification is required. Chemical deep purification mainly includes acid (alkali, salt) treatment and heat treatment. Acid (alkali, salt) treatment mainly removes impurities that exist on the surface of quartz sand particles in the form of gas-liquid inclusions or embedded in quartz sand particles; heat treatment mainly uses high temperature to cause inclusions to burst and reduce gas-liquid impurities (which cannot be completely removed).
[0004] Compared with physical purification, chemical purification is complicated and costly, but chemical treatment is the most effective and indispensable method for preparing high-purity quartz. However, the existing technology has the following problems:
[0005] 1) Before quartz stone is processed into high-purity quartz sand, it needs to undergo pickling, flotation, magnetic separation, gravity separation, high-temperature water quenching, chlorination roasting and other steps. The process is long, the pickling impurity removal efficiency is low and complicated, and exogenous impurities such as iron, sodium, aluminum and other metal elements are easily introduced during the impurity removal process.
[0006] 2) The hydrofluoric acid, hydrochloric acid and nitric acid used in pickling are of high concentration and large amount, which will produce a large amount of fluorine-containing and chlorine-containing wastewater during pickling, increasing the treatment cost.
[0007] In order to solve the above problems, patent CN 116873943A proposes a method for preparing high-purity cristobalite, which uses amorphous silicon dioxide and a silane coupling agent to obtain high-purity cristobalite through sintering, but this quartz sand is in a crystalline state. Summary of the invention
[0008] The technical problem to be solved by the present invention is to provide a method for preparing glassy high-purity quartz sand. The preparation method is simple to operate and the conditions are easy to control. The SiO2 content of the obtained quartz sand can reach more than 99.998% and the specific surface area and density can reach the indicators of existing natural high-purity quartz sand.
[0009] The technical problem to be solved by the present invention is achieved by adopting the following technical solutions:
[0010] One of the purposes of the present invention is to provide a method for preparing glassy high-purity quartz sand, comprising the following steps:
[0011] S1, adding water to nano-scale amorphous silicon dioxide to prepare a slurry, and spray-drying the slurry to obtain nano-silicon dioxide agglomerates;
[0012] S2, subjecting the nano-silicon dioxide aggregates prepared in step S1 to mechanical static pressing to obtain bulk silicon dioxide;
[0013] S3, crushing, calcining and cooling the bulk silicon dioxide prepared in step S2 to obtain glassy high-purity quartz sand.
[0014] The second object of the present invention is to provide a glassy high-purity quartz sand obtained by the above-mentioned preparation method.
[0015] The beneficial effects of the present invention are as follows: the present invention uses nano-scale amorphous silicon dioxide as a raw material, and prepares glassy high-purity quartz sand by pulping, spray drying, mechanical static pressing, mechanical crushing and calcining. The entire preparation process is simple to operate and the conditions are easy to control; and the prepared quartz sand is glassy, and its SiO2 content can reach more than 99.998%, which is a high-end product of high-purity quartz sand; at the same time, the specific surface area and density of the obtained quartz sand can reach the indicators of existing natural high-purity quartz sand. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 This is the XRD pattern of the glassy high-purity quartz sand prepared in Example 1;
[0017] Figure 2This is a microscope picture of the glassy high-purity quartz sand prepared in Example 1. DETAILED DESCRIPTION
[0018] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further described below in conjunction with specific embodiments and diagrams.
[0019] The present invention provides a method for preparing glassy high-purity quartz sand, comprising the following steps:
[0020] S1, adding water to nano-scale amorphous silicon dioxide to prepare a slurry, and spray-drying the slurry to obtain nano-silicon dioxide agglomerates;
[0021] S2, subjecting the nano-silicon dioxide aggregates prepared in step S1 to mechanical static pressing to obtain bulk silicon dioxide;
[0022] S3, crushing, calcining and cooling the bulk silicon dioxide prepared in step S2 to obtain glassy high-purity quartz sand.
[0023] Furthermore, the average particle size of the nano-scale amorphous silicon dioxide is 5-100 nm. Amorphous silicon dioxide is a non-crystalline silicon dioxide. The present invention uses nano-scale amorphous silicon dioxide as a raw material to prepare glassy high-purity quartz sand. High-purity quartz sand in nature is crystalline, while the high-purity quartz sand prepared by the present invention is glassy, which belongs to amorphous state and has a relatively low processing temperature.
[0024] Furthermore, the solid content of the slurry is 5-50%. In the present invention, if the solid content is lower than the range, the powder obtained by spray drying has more fine particles and poor fluidity; if the solid content is higher than the range, the viscosity of the slurry is high and the nozzle is easily blocked.
[0025] Furthermore, the air inlet temperature of the spray drying is 280-350° C., and the air outlet temperature is 80-120° C. In the present invention, the nano-scale amorphous silicon dioxide is transformed into nano-silicon dioxide agglomerates by spray drying.
[0026] Furthermore, the average particle size of the nano-silicon dioxide agglomerates is 100-500 μm. If the particle size is too large, the uniformity will be poor; if the particle size is too small, it will be difficult to prepare. Of course, the particle size of the nano-silicon dioxide agglomerates is also affected by the particle size of the raw material nano-scale amorphous silicon dioxide.
[0027] Furthermore, the pressure of the mechanical static pressure is 150-250MPa, and the time is 10-40min. Since the nano-silicon dioxide powder is very fluffy, if pressure is directly applied to the powder, it will expand again and become loose when the pressure is released, so it is necessary to add water to make a slurry first, and then make large particles by spray drying. In the present invention, the role of mechanical static pressure is to overcome the repulsive force between the nano-silicon dioxide particles, so that the distance between the nano-silicon dioxide particles is closer, so that the product obtained after sintering has less pores.
[0028] Furthermore, the average particle size of the blocky silicon dioxide after mechanical crushing is 50-400 μm.
[0029] Furthermore, the calcination temperature is 1000-1600°C and the time is 3-8h. The crushed blocky silicon dioxide is densified by calcination. If the calcination temperature is too high or the calcination time is too long, crystallization will occur and the energy consumption will be high; if the calcination temperature is too low or the calcination time is too short, it cannot be completely melted and the obtained product has a porous structure. Preferably, the calcination temperature is 1100-1200°C and the time is 5-6h.
[0030] The present invention provides glassy high-purity quartz sand obtained by the above-mentioned preparation method.
[0031] In some specific embodiments, the specific surface area of the glassy high-purity quartz sand is 0.02-0.05 m 2 / g. The glassy high-purity quartz sand prepared by the present invention has a specific surface area and density close to those of natural high-purity quartz sand, and can replace natural high-purity quartz sand.
[0032] Example 1
[0033] Amorphous silicon dioxide with an average particle size of 5 nm is added to water to prepare a slurry with a solid content of 20%; the slurry is spray-dried (the inlet air temperature is 350°C and the outlet air temperature is 120°C) to obtain nano-silicon dioxide agglomerates with an average particle size of 150 μm; the nano-silicon dioxide agglomerates are subjected to mechanical static pressing (pressure of 200 MPa for 0.5 h) to obtain block silicon dioxide; the block silicon dioxide is mechanically crushed into particles with an average particle size of 70 μm, calcined at 1100°C for 6 h, and naturally cooled to obtain glassy high-purity quartz sand with an average particle size of 30 μm.
[0034] Example 2
[0035] Amorphous silicon dioxide with an average particle size of 30 nm is added to water to prepare a slurry with a solid content of 5%; the slurry is spray-dried (the inlet air temperature is 280°C and the outlet air temperature is 80°C) to obtain nano-silicon dioxide agglomerates with an average particle size of 300 μm; the nano-silicon dioxide agglomerates are subjected to mechanical static pressing (pressure of 250 MPa for 0.5 h) to obtain block silicon dioxide; the block silicon dioxide is mechanically crushed into particles with an average particle size of 80 μm, calcined at 1200°C for 5 h, and naturally cooled to obtain glassy high-purity quartz sand with an average particle size of 45 μm.
[0036] Example 3
[0037] Amorphous silicon dioxide with an average particle size of 100 nm is added to water to prepare a slurry with a solid content of 15%; the slurry is spray-dried (the inlet air temperature is 300°C and the outlet air temperature is 110°C) to obtain nano-silicon dioxide agglomerates with an average particle size of 500 μm; the nano-silicon dioxide agglomerates are mechanically statically pressed (the pressure is 150 MPa and the time is 0.5 h) to obtain block silicon dioxide; the block silicon dioxide is mechanically crushed into particles with an average particle size of 90 μm, calcined at 1200°C for 6 h, and naturally cooled to obtain glassy high-purity quartz sand with an average particle size of 50 μm.
[0038] Example 4
[0039] Amorphous silicon dioxide with an average particle size of 70 nm is added to water to prepare a slurry with a solid content of 50%; the slurry is spray-dried (the inlet air temperature is 290° C., the outlet air temperature is 90° C.) to obtain nano-silicon dioxide agglomerates with an average particle size of 200 μm; the nano-silicon dioxide agglomerates are subjected to mechanical static pressing (pressure of 200 MPa, time of 0.5 h) to obtain block silicon dioxide; the block silicon dioxide is mechanically crushed into particles with an average particle size of 70 μm, calcined at 1100° C. for 6 h, and naturally cooled to obtain glassy high-purity quartz sand with an average particle size of 50 μm.
[0040] Comparative Example 1 (without spray drying)
[0041] Amorphous silicon dioxide with an average particle size of 5 nm is subjected to mechanical static pressing (pressure 300 MPa, time 0.5 h) to obtain bulk silicon dioxide; after the pressure is released and taken out, the bulk silicon dioxide cracks, and the bulk silicon dioxide is mechanically crushed into particles with an average particle size of 100 μm, calcined at 1100°C for 6 h, and naturally cooled to obtain opaque high-purity quartz sand with an average particle size of 80 μm.
[0042] Comparative Example 2 (without mechanical static pressure)
[0043] Amorphous silica with an average particle size of 5 nm is added to water to prepare a slurry with a solid content of 20%; the slurry is spray-dried (the inlet air temperature is 350°C and the outlet air temperature is 120°C) to obtain nano-silica agglomerates with an average particle size of 150 μm; the nano-silica agglomerates are calcined at 1100°C for 6 hours and naturally cooled to obtain opaque high-purity quartz sand with an average particle size of 75 μm.
[0044] Comparative Example 3 (Mechanical static pressure is too low)
[0045] Amorphous silicon dioxide with an average particle size of 5 nm is added to water to prepare a slurry with a solid content of 25%; the slurry is spray-dried (the inlet air temperature is 350° C., the outlet air temperature is 120° C.) to obtain nano-silicon dioxide agglomerates with an average particle size of 100 μm; the nano-silicon dioxide agglomerates are mechanically statically pressed (pressure 5 MPa, time 1 h) to obtain block silicon dioxide; the block silicon dioxide is mechanically crushed into particles with an average particle size of 100 μm, calcined at 1100° C. for 6 h, and naturally cooled to obtain glassy high-purity quartz sand with an average particle size of 60 μm.
[0046] Comparative Example 4 (calcination temperature is too low)
[0047] Amorphous silicon dioxide with an average particle size of 8 nm is added to water to prepare a slurry with a solid content of 15%; the slurry is spray-dried (the inlet air temperature is 350°C and the outlet air temperature is 120°C) to obtain nano-silicon dioxide agglomerates with an average particle size of 100 μm; the nano-silicon dioxide agglomerates are subjected to mechanical static pressing (pressure 200 MPa, time 0.5 h) to obtain block silicon dioxide; the block silicon dioxide is mechanically crushed into particles with an average particle size of 110 μm, calcined at 900°C for 6 h, and naturally cooled to obtain glassy high-purity quartz sand with an average particle size of 60 μm.
[0048] Comparative Example 5
[0049] Model ITOA-6 high-purity quartz sand from Unimin Corporation of the United States (natural high-purity quartz sand with an average particle size of 30 μm).
[0050] from Figure 1 and Figure 2 It can be seen that the glassy quartz sand prepared in Example 1 is glassy quartz sand, while the opaque quartz sand prepared in Comparative Examples 1 and 2 is opaque quartz sand.
[0051] The samples prepared in the above examples and comparative examples were measured for the impurity ion content using ICP-OES (inductively coupled plasma optical emission spectrometer, with a detection limit of 1 ppb). The results are shown in Table 1.
[0052] Table 1 Test results of impurity ion content of samples (unit: ppm)
[0053] Al B Ca Cr Cu Fe K Li Example 1 0.368 0.473 0.434 ND ND 0.098 0.043 0.507 Example 2 0.588 0.202 0.898 ND ND 0.334 0.400 0.012 Example 3 0.342 0.187 0.299 ND ND 0.095 0.855 0.798 Example 4 0.353 0.968 0.591 ND ND 0.334 0.570 0.099 Comparative Example 1 0.860 0.675 0.849 0.124 0.020 0.574 0.238 0.028 Comparative Example 2 0.204 0.320 0.194 ND ND 0.803 0.773 0.650 Comparative Example 3 0.844 0.145 0.482 ND ND 0.914 0.399 0.424 Comparative Example 4 0.198 0.156 0.838 ND ND 0.692 0.148 0.105 Comparative Example 5 4.220 0.730 0.204 0.141 0.031 0.605 0.682 0.506 Mg Mn Na Ni P Ti total Example 1 0.007 0.869 0.550 ND ND 0.774 4.123 Example 2 0.965 0.300 0.111 ND ND 0.647 4.457 Example 3 0.489 0.173 0.022 ND ND 0.151 3.411 Example 4 0.317 0.526 0.599 ND ND 0.139 4.496 Comparative Example 1 0.878 0.364 0.316 ND ND 0.246 5.172 Comparative Example 2 0.735 0.014 0.100 ND ND 0.890 4.683 Comparative Example 3 0.255 0.426 0.299 ND ND 0.778 4.966 Comparative Example 4 0.903 0.950 0.606 ND ND 0.213 4.809 Comparative Example 5 0.460 0.150 0.869 ND ND 0.293 8.891
[0054] It can be seen from Table 1 that the total impurity content in the samples prepared in Examples 1-4 is less than 5 ppm, belonging to high-purity quartz sand, and its purity is higher than the natural high-purity quartz sand available on the market.
[0055] The specific surface area and density of the samples prepared in the above examples and comparative examples were measured, and the results are shown in Table 2.
[0056] The specific surface area was tested using the BET method.
[0057] Density test was carried out using the Archimedes drainage method.
[0058] Table 2 Specific surface area and density test results of samples
[0059] <![CDATA[Specific surface area (m 2 / g)]]> <![CDATA[Density (g / cm 3 )]]> Example 1 0.04 2.10 Example 2 0.03 2.13 Example 3 0.02 2.15 Example 4 0.03 2.14 Comparative Example 1 0.73 2.02 Comparative Example 2 2.52 1.95 Comparative Example 3 0.43 2.08 Comparative Example 4 1.06 1.91 Comparative Example 5 0.01 2.20
[0060] As can be seen from Table 2, the specific surface area and density of the samples obtained in Examples 1-4 are comparable to those of natural high-purity quartz sand. Since spray drying is not performed in Comparative Example 1, the specific surface area of the sample obtained becomes larger and is opaque and non-glassy. Since mechanical static pressing is not performed in Comparative Example 2, the sample obtained is also opaque and non-glassy quartz with a large specific surface area. This may be because the pores between the nanoparticles are large and there are still a large number of voids inside after high-temperature calcination. In Comparative Example 3, the pressure of mechanical static pressing is too small. Although glassy high-purity quartz sand can be obtained, the specific surface area is large. Since the calcination temperature in Comparative Example 4 is too low, the silicon dioxide cannot be completely melted into a dense structure, resulting in an increase in the specific surface area.
[0061] In summary, the preparation method provided by the present invention can obtain glassy high-purity quartz sand having a specific surface area and density comparable to those of natural high-purity quartz sand.
[0062] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A method for preparing glassy high-purity quartz sand, characterized in that: The following steps are involved: S1, adding water to nano-scale amorphous silicon dioxide to prepare a slurry, and spray-drying the slurry to obtain nano-silicon dioxide agglomerates; S2, subjecting the nano-silicon dioxide aggregates prepared in step S1 to mechanical static pressing to obtain bulk silicon dioxide; S3, crushing, calcining and cooling the bulk silicon dioxide prepared in step S2 to obtain glassy high-purity quartz sand.
2. The preparation method according to claim 1, characterized in that: The average particle size of the nano-scale amorphous silicon dioxide is 5-100 nm.
3. The preparation method according to claim 1, characterized in that: The solid content of the slurry is 5-50%.
4. The preparation method according to claim 1, characterized in that: The inlet air temperature of the spray drying is 280-350°C, and the outlet air temperature is 80-120°C.
5. The preparation method according to claim 1, characterized in that: The average particle size of the nano-silicon dioxide agglomerates is 100-500 μm.
6. The preparation method according to claim 1, characterized in that: The mechanical static pressure has a pressure of 150-250 MPa and a time of 10-40 min.
7. The preparation method according to claim 1, characterized in that: The average particle size of the blocky silicon dioxide after mechanical crushing is 50-400 μm.
8. The preparation method according to claim 1, characterized in that: The calcination temperature is 1000-1600° C. and the calcination time is 3-8 hours.
9. Vitreous high-purity quartz sand obtained by the preparation method according to any one of claims 1 to 8.
10. The glassy high-purity quartz sand according to claim 9, characterized in that: The specific surface area of the glassy high-purity quartz sand is 0.02-0.05m 2 / g.